Electron beam melting of Inconel 718: effects of processing and post-processing. Issue 5 (24th March 2018) - Nandwana, Peeyush; Kirka, Michael; Okello, Alfred; Dehoff, Ryan
ABSTRACT: This study reports the effect of process temperature on microstructure evolution of electron beam melted Inconel 718. Samples fabricated at 915°C had fine grain boundary δ (∼200 nm) along with coarse intragranular δ spanning through the length of the grains. On the other hand, samples fabricated at 990°C, only had grain boundary δ along with secondary carbides. During hot isostatic pressing, the distribution of carbides governs the grain growth vs. lack of it. The samples fabricated at 990°C having grain boundary carbides had no grain growth owing to the pinning effect of carbides. In contrast, the sample processed at 915°C had significant grain growth owing to dissolution of grain boundary δ phase and absence of grain boundary carbides.